Archaeologists’ perceptions on public outreach and education - Doug Rocks-Macqueen (AP, 2016)
This paper presents the results of a survey of archaeologists’ perceptions of public outreach and education, also known as public archaeology. The results obtained indicate that archaeologists’ views on public archaeology are generally positive but with reservations. Those specific reservations being that public archaeology is not perceived as one of the most important aspects of archaeology. This paper ends with a discussion on exactly what this means for public outreach and education in archaeology.